2016
DOI: 10.1177/0023677216678824
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal micro-computed tomography monitoring of progressive liver regeneration in a mouse model of partial hepatectomy

Abstract: The partial hepatectomy (PH) model is widely used to study liver regeneration. Currently, the extent of regeneration is analyzed by measuring the weight of the liver post-mortem or by magnetic resonance imaging. In this study we aimed to determine whether liver volume gain can be accurately measured using micro-computed tomography (microCT). Approximately 42% of the liver was removed by ligation in C57BL/6 N mice. Mice were divided into two study groups. In group 1 conventional characterization of liver hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Consequently, both spleen and liver are highly contrasted by micro-CT imaging. Anatomical evaluations of the spleen and the liver in normal and regenerative processes using ExiTron nano 12000 have been reported (Das et al., 2016, Will et al., 2017). Importantly, ExiTron nano 12000 does not cause hepatotoxicity and does not lead to pro-inflammatory cytokine release in the liver or serum, thus ensuring a relatively safe approach for longitudinal pharmacology and toxicology studies (Boll et al., 2011, Boll et al., 2013, Liu et al., 2019, Mannheim et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, both spleen and liver are highly contrasted by micro-CT imaging. Anatomical evaluations of the spleen and the liver in normal and regenerative processes using ExiTron nano 12000 have been reported (Das et al., 2016, Will et al., 2017). Importantly, ExiTron nano 12000 does not cause hepatotoxicity and does not lead to pro-inflammatory cytokine release in the liver or serum, thus ensuring a relatively safe approach for longitudinal pharmacology and toxicology studies (Boll et al., 2011, Boll et al., 2013, Liu et al., 2019, Mannheim et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To provide a reference standard, we also quantitatively measured the remnant liver volume via contrast-enhanced μCT, which has been commonly used in clinical settings for hepatic diagnosis 33 . The μCT analysis revealed that liver volume was significantly increased after resection, up to 191.0% ± 35.0% and 218.3% ± 53.8% at day 5 and day 7, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical practice, the linear dimensions, volume, and structure of the liver are examined using traditional imaging techniques such as ultrasound, CT, MRI, and ultrasound elastography. In suspected pathology, the liver parenchyma is examined for its regenerative potential and the risk of liver failure after surgery [17,18].…”
Section: Traditional Methods For Assessing the Linear Dimensions Volmentioning
confidence: 99%
“…Fluorescence microscopy allows evaluating the presence and distribution of specific molecules and investigating cellular events in real time. Recent data obtained with fluorescence imaging provide some insight into the structure and function of normal and pathological liver [17]. For example, the microstructure of hepatocytes was studied using confocal single-photon [94] and multiphoton microscopy (MPM) [95,96].…”
Section: Promising Methods For Assessing the Structure Function Andmentioning
confidence: 99%